2020
DOI: 10.2147/prbm.s269874
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Mediating Role of Cognitive Emotion Regulation in BIS/BAS Sensitivities, Depression, and Anxiety Among Community-Dwelling Older Adults in China</p>

Abstract: Background The behavioral inhibition system (BIS) and behavioral activation system (BAS), which primarily underlie emotions and behaviors, are associated with depression and anxiety. However, the reasons behind these associations require further exploration. Objective This study aims to examine the mediating effects of cognitive emotion regulation between BIS/BAS and depression/anxiety among community-dwelling elderly Chinese. Methods A cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Carver and White (1994) stated earlier that a higher BIS activation can make an individual behaviorally inhibited, meaning to avoid any confrontation or negative outcome, which in turn can lead to more frustration and anxiety. We consequently expect BIS to be related to avoiding, passive coping strategies, as was the case in a study by Sun et al (2020). We hypothesize BAS to be positively correlated to extraversion, adaptive coping strategies such as seeking social support, expressing emotions and reassuring thoughts, and cluster B scales (Sun et al, 2020).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Carver and White (1994) stated earlier that a higher BIS activation can make an individual behaviorally inhibited, meaning to avoid any confrontation or negative outcome, which in turn can lead to more frustration and anxiety. We consequently expect BIS to be related to avoiding, passive coping strategies, as was the case in a study by Sun et al (2020). We hypothesize BAS to be positively correlated to extraversion, adaptive coping strategies such as seeking social support, expressing emotions and reassuring thoughts, and cluster B scales (Sun et al, 2020).…”
mentioning
confidence: 88%
“…Hasking (2006) suggests a positive relationship between BIS and maladaptive coping; and a positive relationship between BAS-Reward Responsiveness and problem solving. Sun et al (2020) examined the mediating role of cognitive emotion regulation in BIS/BAS sensitivity among a community-dwelling, older sample. They found that a higher BIS reactivity was related to maladaptive emotion regulation strategies (e.g.…”
mentioning
confidence: 99%
“…Many studies have further linked emotion regulation strategies to depression (Diedrich et al, 2017 ; Sun et al, 2020 ). As an adaptive strategy, cognitive reappraisal can help reduce negative emotions and improve mental health (Chen et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…These scales were designed to quantify the two systems of the original RST, and thus, do not separate the BIS and FFFS, though attempts have been made to distinguish the systems from items in the BIS/BAS scale (Heym et al, 2008), which may prove useful in uniting findings from studies that examined original RST with the theoretical changes seen in revised RST. Nevertheless, these original scales are still being widely used since the revisions to RST to classify approach/avoidance tendencies (e.g., Balconi et al, 2019; Bossola et al, 2020; Sun et al, 2020). More recent scales have been designed based on the revised RST, such as the Reinforcement Sensitivity Theory Personality Questionnaire (RST-PQ; Corr & Cooper, 2016), Reinforcement Sensitivity Questionnaire (RSQ; Smederevac et al, 2014), Revised Reinforcement Sensitivity Questionnaire (rRST-Q; Reuter et al, 2015), and the Jackson 5 (Jackson, 2009).…”
Section: Psychometric Evaluation Of Rstmentioning
confidence: 99%
“…4 STANDEN, FIRTH, SUMICH, AND HEYM (e.g., Balconi et al, 2019;Bossola et al, 2020;Sun et al, 2020). More recent scales have been designed based on the revised RST, such as the Reinforcement Sensitivity Theory Personality Questionnaire (RST-PQ; Corr & Cooper, 2016), Reinforcement Sensitivity Questionnaire (RSQ; Smederevac et al, 2014), Revised Reinforcement Sensitivity Questionnaire (rRST-Q; Reuter et al, 2015), and the Jackson 5 (Jackson, 2009).…”
Section: Psychometric Evaluation Of Rstmentioning
confidence: 99%